2018
DOI: 10.3389/fnagi.2018.00401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Postural Responses to Visual Perturbations During Fast Pointing

Abstract: People can quickly adjust their goal-directed hand movements to an unexpected visual perturbation (a target jump or background motion). Does this ability decrease with age? We examined how aging affects both the timing and vigor of fast manual and postural adjustments to visual perturbations. Young and older adults stood in front of a horizontal screen. They were instructed to tap on targets presented on the screen as quickly and accurately as possible by moving their hand in the sagittal direction. In some tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 55 publications
4
18
0
Order By: Relevance
“…We found that older adults could make such adjustments, but not as well as the young, in agreement with previous work (Mazaheri et al 2015). This is a similar pattern to the one we had previously found for responses of the hand to target shifts (Zhang et al 2018a). Ageing affected the EMG responses much less than the kinematics, suggesting that it is mainly the execution of the command that is affected, rather than the neural control.…”
Section: Discussionsupporting
confidence: 92%
“…We found that older adults could make such adjustments, but not as well as the young, in agreement with previous work (Mazaheri et al 2015). This is a similar pattern to the one we had previously found for responses of the hand to target shifts (Zhang et al 2018a). Ageing affected the EMG responses much less than the kinematics, suggesting that it is mainly the execution of the command that is affected, rather than the neural control.…”
Section: Discussionsupporting
confidence: 92%
“…The predicted magnitude of the illusion’s effect on interception depends on the time for which the motion has to be extrapolated (the visuomotor delay). We are likely to have underestimated the visuomotor delay for MS and BK because we did not consider the fact that the visuomotor delay is known to increase slightly with age 52 . However, this cannot explain the whole pattern, as for MS the predicted error for embedded motion in the opposite direction than the patch’s motion is mainly small because of his small velocity judgment errors in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to adjust ongoing movements to new visual information has been studied extensively in goal-directed reaching. When a target shifts to a new location, the hand can adjust its trajectory towards the new location within 100-160 ms (Oostwoud Wijdenes et al 2013;Smeets et al 2016;Zhang et al 2018). It is not clear whether similar adjustments are to be expected for the cyclic movements of the feet when walking over a flat surface, because when walking the feet are carefully placed in the medio-lateral direction to maintain balance (Donelan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Another related factor that might influence the presence of movement adjustments is the timing of the perturbation. Hand movement adjustments become stronger for perturbations closer to the end of the movement (Oostwoud Wijdenes et al 2013;Smeets et al 2016;Zhang et al 2018), but this may not be so for foot adjustments because strong responses might lead to a loss of balance. In accordance with this possibility, the foot placement adjustments in response to late perturbations have been reported to be incomplete (Hoogkamer et al 2015;Mazaheri et al 2015) rather than stronger.…”
Section: Introductionmentioning
confidence: 99%